Expression of CD24 is associated with HER2 expression and supports HER2‐Akt signaling in HER2‐positive breast cancer cells. Issue 7 (2nd June 2014) - Hosonaga, Mari; Arima, Yoshimi; Sugihara, Eiji; Kohno, Norio; Saya, Hideyuki
<x xml:space="preserve">Abstract</x> Human epidermal growth factor receptor 2 (HER2)‐positive breast cancer is treated with HER2‐targeted agents, such as trastuzumab and lapatinib, that suppress signaling by phosphatidylinositol 3‐kinase (PI3K)‐Akt and MAPK pathways. However, resistance to HER2‐targeted therapy remains a major clinical problem. Overexpression of CD24 has been detected in many cancers and is associated with a poor prognosis in women with breast cancer. HER2‐positive breast tumors are predominantly positive for CD24, suggesting that the expression of the two molecules is related. To investigate the relation between HER2 and CD24, we overexpressed HER2 in breast cancer cells that were triple‐negative for the estrogen receptor, progesterone receptor and HER2. We found that expression of CD24 was increased by stable overexpression of HER2. Flow cytometry thus revealed that the percentage of CD24‐positive cells was markedly higher in the HER2‐positive fraction than in the HER2‐negative fraction. Knockdown of CD24 in breast cancer cells positive for endogenous HER2 downregulated HER2 expression, whereas knockdown of HER2 did not affect the expression of CD24. Knockdown of CD24 also suppressed the phosphorylation of Akt, which functions downstream of HER2 and PI3K to promote cell survival. Moreover, knockdown of CD24 increased the sensitivity of HER2‐positive breast cancer cells to lapatinib treatment. Our results thus indicate that CD24 supports both the expression of HER2 and the consequent activation of PI3K‐Akt signaling. Furthermore, CD24 may contribute to resistance to HER2‐targeted therapy and, therefore, is itself a potential therapeutic target in HER2‐positive breast cancer.